2015
DOI: 10.1111/joop.12134
|View full text |Cite
|
Sign up to set email alerts
|

The effect of learning goal orientation and communal goal strivings on newcomer proactive behaviours and learning

Abstract: Learning is central to newcomer socialization, but research has rarely investigated the individual motivations that predict learning. Drawing from motivated action theory, this study examines newcomers' learning goal orientation and communal goal strivings, and their effects on the different domains of learning through two separate routes of information-seeking and relationship-building proactive behaviours. In Study 1, we develop and validate a scale for communal goal strivings, demonstrating the empirical di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 127 publications
4
34
0
Order By: Relevance
“…Commonly, these define various domains of knowledge or activities a newcomer has to learn to become a full member of the organization and that lead to more distal indicators of work adjustment, such as in‐role performance, job satisfaction, organizational commitment, intent to leave, and actual turnover (Bauer et al, ; Saks et al, ). In this paper, we used a parsimonious classification similar to Bauer and Erdogan () comprising role, social, and organizational learning that captures the domains represented in previous organizational socialization research (also Tan, Au, Cooper‐Thomas, & Aw, ). The role dimension refers to the clarity of activities and responsibilities, performance expectations, and appropriate behaviors related to one's position in the broader organization.…”
Section: Effects Of Training Lmx and Tmx On Socialization Outcomesmentioning
confidence: 99%
“…Commonly, these define various domains of knowledge or activities a newcomer has to learn to become a full member of the organization and that lead to more distal indicators of work adjustment, such as in‐role performance, job satisfaction, organizational commitment, intent to leave, and actual turnover (Bauer et al, ; Saks et al, ). In this paper, we used a parsimonious classification similar to Bauer and Erdogan () comprising role, social, and organizational learning that captures the domains represented in previous organizational socialization research (also Tan, Au, Cooper‐Thomas, & Aw, ). The role dimension refers to the clarity of activities and responsibilities, performance expectations, and appropriate behaviors related to one's position in the broader organization.…”
Section: Effects Of Training Lmx and Tmx On Socialization Outcomesmentioning
confidence: 99%
“…Research on team newcomers has examined the impact of a wide variety of attributes that facilitate a newcomer’s entry into an intact team. Studies have shown that newcomer traits including proactive personality (Li et al, 2011; Wang et al, 2017), motivation to learn (Tan et al, 2016), and the “Big Five” traits of openness, extraversion, and conscientiousness (Major et al, 2006) are associated with newcomer proactive behaviors during newcomer entry, which may reduce the disruptiveness of a newcomer entry event. Furthermore, newcomers’ creative abilities may increase the criticality of their entry into a team by positively impacting not only the team’s overall creative output but also the creativity of the incumbent team members (Choi & Thompson, 2005), perhaps by stimulating creative idea generation within the team (Nemeth & Ormiston, 2007).…”
Section: Review and Synthesis Of Extant Research On Team Membership Cmentioning
confidence: 99%
“…Although a wide variety of proactive behaviors have been identified (Cooper-Thomas et al, 2012), research suggests the most important behaviors for reducing the potential challenges associated with newcomer entry are information seeking, feedback seeking, and relationship building (Kammeyer-Mueller et al, 2013; Wanberg & Kammeyer-Mueller, 2000). These behaviors may improve team functioning by reducing the burden on incumbent team members to provide informational and social support to the newcomer (Tan et al, 2016). In addition, teams are more likely to adopt the unique knowledge of newcomers who use integrating (i.e., “we,” “our”) as opposed to differentiating (i.e., “I,” “my”) language during task completion (Kane & Rink, 2015).…”
Section: Review and Synthesis Of Extant Research On Team Membership Cmentioning
confidence: 99%
“…Overall, those with high LGO aspire to participate in training activities and developmental processes so that they can apply what they learn (Brett and VandeWalle, 1999). They also seek greater information in the form of direct inquiry, which predicts role, organization, and social learning (Tan et al, 2016).…”
Section: Theoretical Background and Research Hypotheses Learning Goalmentioning
confidence: 99%